Selected aspects of women’s quality of life after mastectomy –preliminary study - Cipora, Elżbieta; Ogrodnik, Bożena; Smoleń, Ewa (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Introduction : In Poland, breast cancer is the leading cause of cancer deaths in females. Early diagnosis and treatment prolongs survival time and affects the quality of life for women. Mastectomy surgery significantly interferes with the biological, psychological, and social spheres. The measurement of quality of life is now an important aspect of clinical trials and a useful element in improving professional care. The aim of the study was to determine quality of life and some of its determinants for patients after mastectomy. Material and methods : The study was conducted at the B. Markiewicz Oncological Hospital in Brzozów in 2013-2014. The study involved 110 women treated for breast cancer. The applied research method was a diagnostic survey, the technique consisted of a survey, and a proprietary questionnaire and Karnofsky’s scale were used as research tools. Results : In the opinion of the majority of respondents, mastectomy changed their quality of life for the worse. Slightly over half of women assessed their quality of life to be at a satisfactory level, while nearly one-third at a good level. The determinants of quality of life were: the need for chemotherapy treatment, the body’s efficiency, the presence of complications, and pain. 59.1% of respondents assessed their current state of health as good. The largest group of respondents (71.3%) assessed their satisfaction with life to be at a satisfactory level. The higher their satisfaction with life, the better the assessment of their health condition. The patients who found their quality of life to be satisfying, also had greater overall satisfaction with life. The average level of women’s efficiency according to Karnofsky was at 68.8. Conclusions : Mastectomy has significantly influenced the quality of life in females. It is advisable to continue studies on the quality of life because monitoring its level and conditions will enable the planning and implementation of activities aimed at improving the biopsychosocial functioning of women with breast cancer.